Content Digital Literation of Biology Textbooks SMA/MA Class XII in Genetic Materials Concept - Yosriah, Ely; Chandra, Edy; Mulyani, Asep; Maryuningsih, Yuyun; Ubaidillah, Mujib (Journal on Biology and Instruction, 2023)
Textbooks can be considered in determining the level of learning opportunities for students. The learning process to support 21st-century skills requires literacy skills, one of which is digital literacy. The purpose of this study was to determine the comparison of digital literacy content in the aspects of elements, skills, levels, and models in Biology textbooks for class XII SMA/MA on the concept of genetic material. The research method used in this research is qualitative content analysis. Overall, the textbooks analyzed so far have not been compiled digitally because they are still very low. Digital literacy must be optimum by being facilitated by appropriate books. Modifying the form of a book with accommodation for higher digital literacy, even though it is a printed book so that it can collaborate with digital media. Therefore, teachers should first analyze the quality of the contents of Biology textbooks with more complex digital literacy content from various publishers, to see a comparison of the quality of each book used in learning.